Biology of Spodoptera litura on natural and artificial diet under laboratory conditions - Hashmi, Ahad Masood; Nadeem, Hafiz Muhammad; Zaman, Muhammad Sohail Qamar; Aizaz, Muhammad; Iqbal, Usama (Journal of Scientific Agriculture, 2023)
Armyworm, Spodoptera litura (Lepidoptera; Noctuidae) is one of the most economically significant insect pests in global agriculture. The current study was performed to study the biology of S. litura under laboratory conditions. In the current study, the biological parameters of pests i.e., egg, larva, pupa and adult along with the duration were determined. The mean incubation period of pests on cabbage, maize and artificial diet was 2.86±0.33, 3.09 ± 0.12 and 3.97±0.77 days, respectively. S. litura had five instars. The mean developmental period of the first, second, third, fourth, fifth and sixth larval instar on cabbage was 3.44±0.11, 2.09±0.12, 4.11±0.12, 3.00±0.20, 6.68±0.23 and 5.94±0.18 days, respectively while 2.81±0.77, 3.55±0.33, 3.64±0.45, 4.43±0.71, 6.55±0.21 and 5.98±0.19 days on the maize, respectively. The mean developmental periods were 3.85±0.54, 3.45±0.63, 3.67±0.67, 4.37±0.82, 6.55±0.23 and 5.30±0.38 days of first, second, third, fourth, fifth and sixth larval instars on artificial diet, respectively. The mean total life period of S. litura was 33.43±5.86 days on cabbage and 34.79±6.95 days on maize while 35.98±7.86 days on an artificial diet. The longest developmental period of S. litura was recorded on the artificial diet while the minimum was on cabbage. The mean developmental period of pupa was 7.50±0.71 days on cabbage, 9.87±0.94 days on maize and 11.63±0.99 days on an artificial diet. Females were short-lived as compared to males. The pre-oviposition, oviposition and post-ovipositional period of S. litura on cabbage were recorded as a minimum while maximum on an artificial diet. The maximum number of eggs laid by females with the highest hatchability on cabbage followed by maize and artificial diet. An artificial diet was not good for pest development and growth as compared to a natural diet i.e., cabbage and maize. The findings will provide basic information about food pests which help in pest management.